Classroom Management Based on Islamic Values to Improve Learning Effectiveness - Sumarni, Sumarni; Basri, Basri; Kaharuddin, Kaharuddin (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the application of Islamic values-based classroom management to improve learning effectiveness. In the context of modern education, teachers are required to understand the relationship between learning management and achieving the institution's vision and mission. Effective classroom management is a crucial factor in developing intellectually superior and morally upright students. Using a descriptive qualitative approach through literature review, this study examines the integration of Islamic values ​​such as honesty, justice, compassion, and responsibility into classroom management. The results of the study indicate that the application of Islamic values ​​through the arrangement of the learning environment, educational interactions, character-based discipline, and the use of educational technology can create a conducive and spiritual learning atmosphere. Therefore, Islamic values-based classroom management is a strategic alternative in developing students with high moral and spiritual integrity.